The impact of influencers on the decision-making process regarding the purchase of the brand product - Gajanova, Lubica; Majerova, Jana; Nadanyiova, Margareta (Business, Management and Economics Engineering, 2020)
Purpose – the aim of this paper is to study the impact of influencers on the decisionmaking process regarding the purchase of the brand product.Research methodology – the method of collecting data through a questionnaire and the contingency analysis to process the data were chosen for this research.Findings – the research revealed quite a degree of distrust of Slovak consumers in influencer marketing. This may be partly explained by the singularity of Slovaks and partly by the limitations of research.Research limitations – the limitation of research may be the fact that it is not possible to draw clear conclusions solely from the perspective of consumers because their actual view may differ from reality. To remove limitations of this kind it is advisable to repeat the questioning on another sample of respondents.Practical implications – the results are anticipated to enhance and deepen the understanding of previous practice of brand managers. The findings should be beneficial for improving the attractiveness of marketing communication and thus higher competitiveness.Originality/Value – the research population has been surveyed not only on flat-rate basis because the segments vary significantly in their perception of influencers’ impact.